Сутність будівельної діяльності: теоретичний погляд - Квасніцька, Ольга Олексіївна; Квасницкая, Ольга Алексеевна; Kvasnickaja, Ol'ga (My University, 2011)
In the present publication is proposed revision of the concept of «capital construction». The author is inviting to debate on issues concerning the phenomenal nature of construction activity, the evolution of this concept in the context of economic development activities and economic links. The analysis of scientific approaches to the legal category of «construction», a comprehensive definition of the characteristic signs of construction activity, its components, allowed to offer the author's definition of construction activities, as a form of economic activity, the content of which is the aggregate action of business entities and other participants of economic relations aimed at building ( construction) of the objects (product) development, including with the organizational, economic and techno-economic components.
Квасніцька О. О. Сутність будівельної діяльності: теоретичний погляд / О. О. Квасніцька // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 413-423.
Keywords: будівельна галузь; будівельна діяльність; капітальне будівництво; містобудівна діяльність; об'єкти будівництва; господарське правове регулювання; строительная отрасль; строительная деятельность; капитальное строительство; градостроительная деятельность; объекты строительства; хозяйственное правове регулирование; building sector; construction activity; capital construction; urban development; construction of objects; Business legal regulation